Effectiveness of using video tutorials in PJOK lessons during the Covid 19 Pandemic - Ferdiansyah, Handy (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to determine the level of effectiveness of video tutorial learning media on PJOK subjects for class IX students of SMP Negeri 1 Baranti. The method used in this research is quantitative research with a descriptive approach. Quantitative research is research based on the philosophy of positivism, focusing on objective facts that have been investigated by quantitative means. The population of this study were all students of class IX SMP Negeri 1 Baranti a total of 60 students. Due to the fact that the population is less than 100, this study uses the entire sample. Data collection techniques used in this study were interviews, questionnaires, and documentation. The data analysis technique of this research used descriptive quantitative analysis in the form of percentages. Based on the results of the study, it is known that the results of the analysis of 4 indicators namely teaching quality, teaching level, incentives, and data time obtained an average of 83.5% indicating the use of video tutorials is very effective in implementing PJOK learning. Thus, it can be concluded that the use of video tutorials in PJOK lessons during the Covid 19 Pandemic is very effective.